ANALISIS MODEL PERTUMBUHAN IKAN BERONANG TULIS (SIGANUS JAVUS) DARI HASIL TANGKAPAN NELAYAN KOTA TARAKAN - Achyani, Ratno; Firdaus, Muhammad; Salim, Gazali (Jurnal Harpodon Borneo, 2012)
Siganus javus is one type of fish that has a lot of potential that is still not fully utilized where these fish contain protein which is high at around 69.2% (weight of wet) and 18.5% (weight of dry). The research objective is to analyze biotechnical of Model Growth absolute, allometri growth of Siganus javus. Methods of research using descriptive method. The scope of this study is the variable of growth absolute, the growth of allometri of Siganus javus. Data collection techniques using survey research design. Techniques of sampling Siganus javus using sampling with purposive sampling method. Capture as much as 12 times the sampling, each taking a maximum of 10 fish due to sampling of endemik is taking place so rarely found. The results obtained using the absolute growth in von Bertalanffy models Siganus javus of sex of male is Lt = 32,495 (1–2,718280.0091 ( t+2,091)) (r =0,627 dan n=59) and than sex of female is Lt = 38,128 (1–2,71828- 0.0172 (t + 1,7889 ))(r =0,648 dan n=41). The models of growth allometri Siganus javus for sex of male obtained values b<2.608 are allometri of negative and than for female sex obtained values b<2.644 are allometri of negative. Keywords : Siganus javus, growth of absolute, growth of Allometri, city of Tarakan